EDEMA PARU KARDIOGENIK AKUT - Rampengan, Starry H. (Jurnal Biomedik : JBM, 2014)
Abstract: Acute cardiogenic pulmonary edema is a common disease, harmful and lethal with a mortality rate 10-20%. Cardiogenic pulmonary edema or edema volume overload due to an increase of pulmonary capillary hydrostatic pressure that causes the increase of transvascular fluid filtration. The increase of pulmonary capillary hydrostatic pressure is usually caused by the increase of pressure in the pulmonary veins that occur due to the increase of left ventricular end-diastolic pressure and left atrial pressure. Clinical features of cardiogenic pulmonary edema are inter alia shortness of breath that is associated with a history of chest pain and heart disease. Cardiogenic pulmonary edema is one of medical emergencies that need early medical treatment after the diagnosis is established. The management includes supportive treatment to maintain lung function (such as gas exchange, organ perfusion), where as the main cause should be investigated and treated as soon as possible whenever possible. The principle of management are adequate oxygen distribution, fluid restriction, and maintain cardiovascular function. The initial consideration are clinical evaluation, ECG, chest x-ray and blood gas analysis.Keywords: acute cardiogenic pulmonary edema, managementAbstrak: Edema paru kardiogenik akut merupakan penyakit yang sering terjadi, merugikan dan mematikan dengan tingkat kematian 10-20 %. Edema paru kardiogenik atau edema volume overload terjadi karena peningkatan tekanan hidrostatik dalam kapiler paru yang menyebabkan peningkatan filtrasi cairan transvaskular. Peningkatan tekanan hidrostatik kapiler paru biasanya disebabkan oleh meningkatnya tekanan di vena pulmonalis yang terjadi akibat meningkatnya tekanan akhir diastolik ventrikel kiri dan tekanan atrium kiri. Gambaran klinis edema paru kardiogenik yaitu adanya sesak napas tiba-tiba yang dihubungkan dengan riwayat nyeri dada dan adanya riwayat sakit jantung. Edema paru kardiogenik merupakan salah satu kegawatan medis yang perlu penanganan medis secepat mungkin setelah ditegakkan diagnosis. Penatalaksanaan utama meliputi pengobatan suportif yang ditujukan terutama untuk mempertahankan fungsi paru (seperti pertukaran gas, perfusi organ), sedangkan penyebab utama juga harus diselidiki dan diobati segera bila memungkinkan. Prinsip penatalaksanaan meliputi pemberian oksigen yang adekuat, restriksi cairan, mempertahankan fungsi kardiovaskular. Pertimbangan awal yaitu evaluasi klinis, EKG, foto toraks dan AGDA.Kata kunci: edema paru kardiogenik akut, tatalaksana